SIGNIFICANCE OF SANDSTONES INTERBEDDED IN THE JURASSIC BASALTS OF THE BALAGNE OPHIOLITIC NAPPE (CORSICA, FRANCE) - Rossi, Philippe; Durand-Delga, Michel (Ofioliti, 2007)
The Balagne Nappe which includes a thick ophiolitic succession, has an isolated external western position and is underlain by Eocene rocks over the autochthonous Corsican basement. The nappe consists, from base to top, of: 1) basaltic pillow lavas up to 1 km thick, 2) oceanic sediments (radiolarites, limestones showing diverse facies, particularly pelagic, pelites with interbeds of “Palombini”-type limestones, and 3) detrital formations ranging from the Albian- Cenomanian to Middle Eocene. The trace element content of the basalts of the Balagne Nappe s.l. is characteristic of enriched mid-oceanic ridge basalts (EMORB). In contrast, lavas of the more eastern Ligurian Units, such as the Inzecca Unit (Upper ‘Schistes lustrés’), have an N-MORB character. We can thus define a marginal “Balagne-Ligurian domain”. In their lower part close to the gabbroic substratum, near Piana di Castifao, the Jurassic basalts have a level of feldspathic and micaceous quartzitic sandstone with calcareous cement (Baud, 1975). This level, 3 m thick, is intercalated within two 8-m layers of basaltic breccia (exploded pillows), sandwiched between flows of pillow lavas in places showing normal polarity. This rules out a tectonic hypothesis for the contacts at the base and top of the sandstones, as both contacts are clearly stratigraphic. The top of the sandstones is coarse grained, with lithic debris of continental origin and basalt fragments. The heavy minerals originate either from the oceanic or continental material. Zircons are particularly abundant and well preserved, which indicates limited transport. The typological study, according to Pupin’s diagram (1980), reveals that zircons plot in the field overlapping that of zircons from calc-alkaline granites (s.l.), highly abundant in the Corsican-Sardinian batholith. The Piana di Castifao sandstone interbed is the only known example in the Corsican Ligurian ophiolites. A similar thin bed has been described from the top of the ophiolitic sequence of the “Lago Nero-Replatte Nappe” to the east of Briançon in the French-Italian Alps. Similarly, in the Queyras region West of Mount Viso were reported sands and gravels with granite clasts, here there are underlying pillow basalts extruded over a serpentinite substratum. In both cases (east of Briançon and Queyras), no geological nor geochemical indications were found to constrain the position of the continent that supplied the detrital material. The detrital material originated from a continental source similar to that of Piana di Castifao. The Balagne-Ligurian domain of the Ligurian Ocean must therefore have been situated, during the Jurassic, relatively close to the Western European continental margin, as indicated by the geochemical facies of the EMORB, the basement fragments within the San Colombano supra-ophiolitic limestones, and the Piana di Castifao quartzitic interbed. The eastern margin of the Ligurian Ocean was also characterized by continental detritus as shown in the Cretaceous External Ligurides in the Northern Apennines.